The Study of Coconut Sugar Produsen in Karang BendoVillage Ponggok District Blitar Regency: The Study of Coconut Sugar Produsen in Karang BendoVillage Ponggok District Blitar Regency - Mochmad Anis (Universitas Islam Balitar, 2019)
Cooperation is an action in the job which is done by two or more people to gain the same purpose. This researh aims to know about coconut sugar production in the Karangbendo Village Ponggok District Blitar Regency.The kind of research which is used is qualitative research with phenomenology approach. This approach focused on the interview that is done deeply about the phenomena which is experienced by the informan. Subject in the research is a coconut sugar production while the object is a cooperation between the owner of coconut sugar producer. The data analysis technique descriptve analysis. The result of this reserch is there are two kinds of cooperation between the owner and the producer; they are “tampan” and ‘ounce”. Each cooperation model has their own differences.